2013
DOI: 10.3892/or.2013.2731
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin regulates SH-SY5Y cell growth through downregulation of BDNF via miR-16

Abstract: Brain-derived neurotropic factor (BDNF) is a member of the neurotropin family. High levels of BDNF are associated with more aggressive malignant behavior in human cancer. In the present study, we observed the effect of cisplatin on BDNF expression in SH-SY5Y cells and investigated the mechanism of cisplatin in inducing the apoptosis of SH-SY5Y cells. Our results revealed that the expression of BDNF was obviously decreased in cisplatin-treated SH-SY5Y cells. In addition, the 3'-untranslated region of BDNF was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Silio prediction and reporter system indicated that the level of BDNF, a central node in the miR-mRNA regulatory network, can be post-transcriptionally modulated by upregulated microRNA-30a-5p [31]. Yun reported that cisplatin can downregulate the expression of BDNF through increasing microRNA-16 to inhibit the proliferation of SH-SY5Y cells in vivo and vitro [32]. Our previous study indicated that PFOS most likely acted through microRNA-22 inhibiting the expression of BDNF in SH-SY5Y cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…Silio prediction and reporter system indicated that the level of BDNF, a central node in the miR-mRNA regulatory network, can be post-transcriptionally modulated by upregulated microRNA-30a-5p [31]. Yun reported that cisplatin can downregulate the expression of BDNF through increasing microRNA-16 to inhibit the proliferation of SH-SY5Y cells in vivo and vitro [32]. Our previous study indicated that PFOS most likely acted through microRNA-22 inhibiting the expression of BDNF in SH-SY5Y cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, treatment of SH-SY5Y cells with free cisPt elicits slightly more cytotoxic effects than HFt-cisPt at higher concentrations (above 10 µM, Supplementary Figure S1), although other studies showed cytotoxicity of cisPt only at very high concentrations (e.g., Refs. [52,53]). …”
Section: Discussionmentioning
confidence: 99%
“…cisplatin was also shown to increase production of microRNA-16 (miR-16) in neuroblastoma cells, which in turn reduced the levels of BDNF in a concentration-dependent manner (43). inhibition of BDNF production resulted in stunted neuroblastoma tumor growth in vivo (43) suggesting that, at least in part, BDNF's antagonism of cisplatin efficacy is due to the compensation of decreased BDNF levels mediated by cisplatin's activation of miR-16.…”
Section: Bdnf: a Governor Of Chemotherapeutic Sensitivitymentioning
confidence: 99%
“…inhibition of BDNF production resulted in stunted neuroblastoma tumor growth in vivo (43) suggesting that, at least in part, BDNF's antagonism of cisplatin efficacy is due to the compensation of decreased BDNF levels mediated by cisplatin's activation of miR-16. other miRs that act antagonistic to BDNF production include MiR-206 in gastric cancer (44) and MiR-107 in non-small cell lung cancer (2).…”
Section: Bdnf: a Governor Of Chemotherapeutic Sensitivitymentioning
confidence: 99%